The effect of landing surface on landing error scoring system grades - Jacobs, K.; Riveros, D.; Vincent, H. K.; Herman, D. C. (Sports Biomechanics, 2021)
Different landing surfaces may affect lower extremity biomechanical performance during athletic tasks. The magnitude of this effect on clinical screening measures such as jump-landings is unknown. This study determined the effect of court (CS), grass (GS), and tile (TS) surfaces on Landing Error Scoring System (LESS) grades. A repeated-measures design was used. A total of 40 (21F, 19M; mean age=23.8±2.4yr) recreational athletes performed a jump-landing task on three different landing surfaces. 2D videography recorded jump-landings in the frontal and sagittal planes. A 2-3 (sex by surface) mixed-model repeated-measures analysis of variance was used to examine main and interaction effects associated with surface and sex. No significant sex by landing surface interactions existed for LESS grades. No significant differences were observed on LESS grades for the main effect of surface (CS=4.83±1.31 points; GS=5.01±1.40 points; TS=5.09±1.86 points; all p>0.05). Correlations were found between LESS grades among different conditions (r range=0.587-0.611; all p<0.001). Commonly used jump-landing surfaces for clinical biomechanical evaluations do not affect LESS grades, suggesting generalisability as a screening tool for anterior cruciate ligament injury risk in different sport environments.